THE EDUCATIONAL PHILOSOPHY OF JOHN DEWEY AND PRACTICE EDUCATION IN PUBLIC SCHOOL - Francisco, Alyson Bueno [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2019)
The educational practices in the vision of Dewey are fundamental in the experiments by the democratic process of production possibilities of knowledge with practice in the act of acting. The Dewey method was founded by philosophical conceptions of empiricism and experimentalism, which in the early 20th century, the American education experiencing the problem of dualities between the theoretical rigor of the educators and the lack of interest of the students. Dewey turns the power of scientific knowledge in the Act of doing through the educational and democratic practices by testing the assumptions and knowledge is not a finalist to achieve the results planned previously, but the importance is in the possibilities to achieve and in attempts in the middle (process) of the investigation. The educational practice of Dewey can be applied in various areas of knowledge, as the study of the environment in geography, school of chemistry laboratory and experimental samples to get the didactic and the observation on the part of students and arousing curiosity and knowledge. In the proposal of Dewey scientific knowledge is not separated from the educational knowledge, being that science needs to be translated into a language didactics and applied in the classroom. In the current context of development of environmental education, Dewey is a thinker who contributes in practical activities, whose small actions can awaken consciousness and change the world.
Keywords: action; democracy; experience; method